A selection methodology of flowback treatment technologies and water reuse in hydraulic fracturing in source rocks – a strategy to reduce the environmental impacts in Colombia - Usuriaga-Torres, José-Manuel; Aranguren Campos, Fabian Alexis; Calderón Carrillo, Zuly (CT&F - Ciencia, Tecnología y Futuro, 2018)
The development of unconventional reservoirs (source rocks) around the world in the last years intensified the use of hydraulic fracturing as stimulation technique in the petroleum industry. Nevertheless, the amount of water used for its execution, the legal restrictions implemented in certain regions for the application of this technology and the possible environmental impact generated, are issues to take into account. In that way, petroleum industry has begun the implementation of technologies for post-frac flowback treatment of these kinds of reservoirs with the aim of converting those waste volumes into an important asset for recurrent hydraulic fracturing operations. The water cycle into these operations begins with the capture of this resource at surface and then, it is mixing with chemicals and proppant to generate the fracturing fluid, which is pumped to the well to create the fractures in the target formation. Once the well starts producing, a fraction of the water injected during the fracturing operation along with formation water, are back produced to surface and finally treated or injected through disposal wells. Given that in Colombia the development of unconventional reservoirs is on its very preliminary phase, there are no studies related to the flowback treatment, which is a sensitive issue in making decisions to develop this energy resource in the country. Hence, this research proposes a methodology for selecting technically technologies suitable for flowback treatment in unconventional reservoirs in Colombia. A review of technical parameters and experiences in a real scale of different technologies, a sensitivity analysis of four water stability indexes, a correlation between flowback physical chemical parameters of a geological formation similar to Colombian geological formation and an economic analysis are presented. The best option always arises from the higher operational efficiency at the lowest cost.